Persepsi Industri Perhotelan Terhadap Kesiapan Kerja Mahasiswa Prodi Tata Boga Politeknik Negeri Balikpapan - Ria Setyawati; Syahrul Karim (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2020)
The aim of this research is to know the perception of the hospitality industry with the students’ readiness to work in the culinary department which includes communication skills, ability to cooperate, the ability of self-reliance, creativity, basic ability, and ability to look. This research used ex-post facto capital with the quantitative approach. The research subject used 25 employees of 5 hotels that consist of some job positions such as a head of HRD, Executive Chef, Sausage Chef, Chef de Partie, Head of Waiter from some hotels that have been used for students to do On the Job Training. Data collection techniques using a poll with a scale model Likert 5 alternative answers. Data analysis used with descriptive statistics with 6 independent variables. This research found five results that consist of: First, the perception of employees hotel toward students’ communication skills is 60% with a very high category. Second, the perception of employees hotels toward students’ teamwork ability is 24% with a very high category. Third, the perception of employees hotels toward students’ autonomy ability is 20% with a very high category. Fourth, the perception of employees hotels toward students’ creativity ability is 32% with a very high category. Fifth, the hotel employee's perception of the basic ability of the students according to industry perception as much as 64% with a very high category. Six, the perception of employees hotel toward students’ appearance ability is 24% with high category Keywords: perception, job readiness, students’ skillABSTRAKPenelitian ini bertujuan untuk mengetahui persepsi industri terhadap kesiapan kerja mahasiswa yang meliputi kemampuan berkomunikasi, kemampuan bekerjasama, kemampuan kemandirian, kreatifitas, kemampuan dasar dan kemampuan berpenampilan.Penelitian ini merupakan penelitian ex-post facto dengan pendekatan kuantitatif.Subjek dari penelitian ini yakni sebanyak 25 karyawan dari 5 hoteldengan jabatan pekerjaan pimpinan HRD, Executif Chef, Sause Chef, Chef de Partie, Head Waiter dari hotel yang telah digunakan mahasiswa untuk Praktek Kerja Lapangan. Teknik pengumpulan data menggunakan angket dengan model skala likert 5 alternatif jawaban.Analisis data yang digunakan dengan statistk deskriptif dengan 6 variabel bebas. Penelitian ini menghasilkan 5temuan antara lain:Pertama, persepsi karyawan hotel terhadap kemampuan berkomunikasi mahasiswa sebanyak 60% dengan kategori sangat tinggi. Kedua, persepsi karyawan hotel terhadap kemampuan bekerjasama mahasiswa sebanyak 24% dengan kategori sangat tinggi.Ketiga, persepsi karyawan hotel terhadap kemampuan kemandirian mahasiswa sebanyak 20% dengan kategori sangat tinggi.Keempat, persepsi industri terhadap Kemampuan kreatifitas mahasiswa menurut persepsi industri sebanyak 32% dengan kategori sangat tinggi.Kelima, persepsi karyawan hotel terhadapkemampuan kemampuan dasar boga mahasiswa menurut persepsi industri sebanyak 64% dengan kategori sangat tinggi.Keenampersepsi karyawan hotel terhadapkemampuan berpenampilan mahasiswa menurut persepsi industri sebanyak 24% sangat tinggi. Kata kunci :persepsi, kesiapan kerja, kemampuan mahasiswa